2019
DOI: 10.1186/s12882-019-1550-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of hydrogen sulfide against uremic accelerated atherosclerosis through cPKCβII/Akt signal pathway

Abstract: Background Cardiovascular disease is the most common complication and leading cause of death in maintenance hemodialysis patients. The protection mechanism of hydrogen sulfide (H2S) and the specific role of conventional protein kinase C βII (cPKCβII)/Akt signaling pathway in the formation of atherosclerosis is still controversial. Methods 8-week-old male ApoE−/− mice were treated with 5/6 nephrectomy and high-fat diet to make uremia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…The role of CSE/H 2 S system and TGF-β/Smad pathway in atherogenic process was discussed respectively in other studies. Meanwhile, we confirmed the protective effect of H 2 S regulating cPKCβII/Akt pathway in UAAS patients against atherosclerosis formation and cardiovascular disease progression in our previous study [16]. But whether other signaling pathways may also participate in this process and how the 5/6 nephrectomy and CSE/H 2 S system affect the plaque formation were still unclear in the previous study.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The role of CSE/H 2 S system and TGF-β/Smad pathway in atherogenic process was discussed respectively in other studies. Meanwhile, we confirmed the protective effect of H 2 S regulating cPKCβII/Akt pathway in UAAS patients against atherosclerosis formation and cardiovascular disease progression in our previous study [16]. But whether other signaling pathways may also participate in this process and how the 5/6 nephrectomy and CSE/H 2 S system affect the plaque formation were still unclear in the previous study.…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, abnormalities of H 2 S and TGF-β/Smad signaling pathway could lead to UAAS development in chronic hemodialysis patients with diabetic nephropathy [15]. We also found that endogenous CSE/H 2 S system may protect against the formation of UAAS via cPKCβII/Akt signal pathway [16]. But how the 5/6 nephrectomy and CSE/H 2 S system affect the plaque formation and whether other signaling pathways may also participate in this process were still unclear in the previous study.…”
Section: Introductionmentioning
confidence: 58%
“…In the study by Testai et al [ 130 ] the H₂S-donor 4-carboxyphenyl isothiocyanate protected against ischemia/reperfusion (I/R)-mediated myocardial tissue injury [ 130 ]. The endogenous cystathionine-γ-lyase (CSE)/H₂S system protected arteries from atherosclerosis through modulating cPKCβII/Akt signal pathway in mouse uremia accelerated atherosclerosis (UAAS) model [ 131 ]. Future studies may uncover whether ITCs modulate this pathway.…”
Section: Mechanism Of Cardio- and Neuroprotective Effectmentioning
confidence: 99%
“…SFN prevents atherosclerosis through modulating various pathways involved in oxidative stress, inflammation, and lipid metabolism and also prevents restenosis of arteries. SFN inhibits key events in atherosclerosis development and progression through MAPK/AP-1/NF-κB [ 146 ] and Nrf2/ARE pathways and possibly the cPKCβII/Akt (Akt-protein kinase B) signal pathway [ 131 ]. SFN improves morphological, histological, and echocardiographic parameters in MI more than mechanical postC, secondary to upregulation of antioxidant response, inhibition of oxidative stress, lipid peroxidation, inflammation, apoptosis and autophagy [ 62 ].…”
Section: Mechanism Of Cardio- and Neuroprotective Effectmentioning
confidence: 99%
“…Another study reports that treatment with alpha-lipoic acid or NaHS can attenuate diabetes-induced vascular dysfunctions in SMC in rats by elevating H 2 S levels and reducing autophagy by targeting the AMPK/mTOR pathway [ 202 ]. Similarly, NaHS treatment prevents the development of atherosclerosis in uremic-accelerated atherosclerotic ApoE -/- mice through the suppression of TGF-β/Smad3 and activation of the conventional PKC βII/AKT/eNOS pathway [ 203 , 204 ]. A recent study also showed that treatment of diabetes-stimulated atherosclerotic cells and mice with GYY4137 significantly reduces the elevation of pro-inflammatory activities by promoting the activation of PI3K/AKT and the deactivation of NLRP3 and Toll-like receptor-4 signaling [ 205 , 206 ].…”
Section: H 2 S and Cvdsmentioning
confidence: 99%